Tunable Cellular Localization and Extensive Cytoskeleton-Interplay of Reflectins - Song, Junyi; Liu, Chuanyang; Li, Baoshan; Liu, Liangcheng; Zeng, Ling; Ye, Zonghuang; Mao, Ting; Wu, Wenjian; Hu, Biru (Frontiers in Cell and Developmental Biology, 2022)
Reflectin proteins are nature copolymers consisting of repeated canonical domains. They are located in a biophotonic system called Bragg lamellae and manipulate the dynamic structural coloration of iridocytes. Their biological functions are intriguing, but the underlying mechanism is not fully understood. Reflectin A1, A2, B1 and C were found to present distinguished cyto-/nucleoplasmic localization preferences in the work. Comparable intracellular localization was reproduced by truncated reflectin variants, suggesting a conceivable evolutionary order among reflectin proteins. The size-dependent access of reflectin variants into the nucleus demonstrated a potential model of how reflectins get into Bragg lamellae. Besides, RfA1 was found to extensively interact with the cytoskeleton, including its binding to actin and enrichment at microtubule organizing center microtubule. This implied the cytoskeleton system plays fundamental role during the organization and transportation of reflectin proteins. Findings presented here provide evidence to get an in-depth insight into the evolutionary processes and working mechanism of reflectins, as well as novel molecular tools to achieve tunable intracellular transportation.